Optimizing Fully Homomorphic Encryption Algorithm using RSA and Diffie- Hellman Approach in Cloud Computing - Negi, Aparna; Goyal, Anshika (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is a technology where user can store their data and any application software on it. With the use of this technology user need not to worry about the cost of hardware installation and their maintenance cost. Hence, the cloud computing security becomes the current research focus. To secure the cloud data, Encryption Scheme is used. Different encryption techniques used for security purpose like Fully Disk Encryption and Fully Homomorphic Encryption. FDE encrypts the entire disk and FHE encrypts the particular functions. FHE is used to secure the cloud data from exploitation during the computation. In this research paper, FHE encryption scheme is optimized in which the Encryption Time, Probability of Attacks and Space Used by encrypted data is reduced using RSA and Diffie- Hellman Algorithm. RSA Algorithm is applied to improve performance of FHE schemes. The Diffie- Hellman algorithm is also applied for the secure channel establishment in the fully homomorphic encryption It has been analyzed that RSA algorithm based FHE performs well as compared to Diffie- Hellman algorithm.